A practitioner's guide to public relations research, measurement and evaluation - Stacks, Don W. (Public relations collection, 2010)
This volume introduces the reader to the world of research and public relations research in particular. It takes a best practices approach--one that focuses on taking the appropriate method and rigorously applying that method to collect the data that best answer the objectives of the research. It also presents an approach to public relations that focuses on establishing the profession's impact on the client's return on investment in the public relations function, whether that function be aimed at internal or external audiences. By the end of the book, the reader will not be a research expert but will understand why and how research is conducted. Further, the reader will be able to apply best practice standards to any research done by supply side vendors or internal research departments.